Open veins of Latin America five centuries of the pillage of a continent - Galeano, Eduardo (New York Monthly Review Press, 1997)
Since its U.S. debut a quarter-century ago, this brilliant text has set a new standard for historical scholarship of Latin America. It is also an outstanding political economy, a social and cultural narrative of the highest quality, and perhaps the finest description of primitive capital accumulation since Marx.
Includes bibliographical references (p. 287-305) and index.
Keywords: Latin America--Economic conditions